2022
DOI: 10.1002/cncr.34326
|View full text |Cite
|
Sign up to set email alerts
|

The yield and effectiveness of breast cancer surveillance in women with PTEN Hamartoma Tumor Syndrome

Abstract: BACKGROUND:Women with PTEN Hamartoma Tumor Syndrome (PHTS) are offered breast cancer (BC) surveillance because of an increased BC lifetime risk. Surveillance guidelines are, however, expert opinion-based because of a lack of data. We aimed to assess the yield and effectiveness of BC surveillance and the prevalence and type of breast disease in women with PHTS. METHODS: Sixty-five women with PHTS who visited our center between 2001 and 2021 were included. Surveillance consisted of annual magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…Both the sensitivity (100%) and speci city (82%) of the combined modalities were found to be high. However, consistent with ndings from studies in high-risk populations (MRI: 71-96%, mammography: 19-51%) [11][12][13], MRI demonstrated superior sensitivity (100%) compared to mammography (50%) when these modalities were assessed independently [10]. Similarly, despite the individual speci city of mammography (92%) and MRI (84%) being both adequate, MRI alone was responsible for the diagnosis of BC in 3 out of 5 women who underwent both imaging modalities.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Both the sensitivity (100%) and speci city (82%) of the combined modalities were found to be high. However, consistent with ndings from studies in high-risk populations (MRI: 71-96%, mammography: 19-51%) [11][12][13], MRI demonstrated superior sensitivity (100%) compared to mammography (50%) when these modalities were assessed independently [10]. Similarly, despite the individual speci city of mammography (92%) and MRI (84%) being both adequate, MRI alone was responsible for the diagnosis of BC in 3 out of 5 women who underwent both imaging modalities.…”
Section: Introductionsupporting
confidence: 81%
“…However, the speci c appearance of BCs in women with PHTS remains under-explored. Considering the relatively high prevalence of benign breast lesions (BBLs) (46%) in this group [10], studies describing both benign and malignant imaging characteristics could further increase sensitivity and speci city of the surveillance program. Additionally, such data could inform expert opinion-based guidelines and potentially lead to a reevaluation of mammography use, speci cally in young women with PHTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hoxhaj et al reported a CDR with MRI of 45 per 1000 rounds (95% CI, 20–94) in PTEN mutation carriers. This is comparable to (or even higher than) the CDR of MRI in BRCA1/2 mutation carriers suggesting that the two high risk groups are indeed comparable and the imaging surveillance should be the same 54 . The role of screening with MRI for women with pathogenic variants of ATM, CHEK2, and PALB2 mutation carriers is currently investigated, suggesting a similar beneficial effect 55 …”
Section: Literature Searchmentioning
confidence: 81%
“…This is comparable to (or even higher than) the CDR of MRI in BRCA1/2 mutation carriers suggesting that the two high risk groups are indeed comparable and the imaging surveillance should be the same. 54 The role of firstand second-degree family history, including unaffected relatives, and allows for multiple genes with variable penetrance. 28,59,60 Also women with a personal history of breast cancer have an elevated risk of breast cancer recurrence with a cumulative incidence of 5.4% in 5 years.…”
Section: Women At High Risk For the Development Of Breast Cancermentioning
confidence: 99%